Pemanfaatan Teknologi Breakthrough Innovation Enzim dalam Mengoptimalkan Pengelolaan Limbah Organik: Pemanfaatan Teknologi Breakthrough Innovation Enzim dalam Mengoptimalkan Pengelolaan Limbah Organik - .Vebrianti, Lusita (Journal of Sustainable Community Development (JSCD), 2024)
This article aims to discuss the application of POCI (Liquid Organic Fertilizer) enzyme technology from MASARO in organic waste management in Rawajati Village, South Jakarta. The utilization of POCI enzymes in organic waste management in Rawajati is carried out with the aim of increasing the effectiveness and efficiency of organic waste treatment to empower the community to manage waste independently. This program is carried out through continuous training and mentoring provided to the Rawajati community and monitoring the sustainability and effectiveness of organic waste treatment using POCI enzymes. The implementation results show that some Rawajati communities have managed organic waste more effectively and efficiently when using the enzyme. As part of Kampung Proklim, Rawajati is now showing a stronger commitment to sustainable environmental management. Further assistance is needed to strengthen the sustainability of the program and expand community involvement, making MASARO technology an innovative solution that has the potential to be applied in other urban areas.